Determinación del plazo para iniciar la tramitación administrativa del régimen semiabierto para garantizar el debido proceso y evitar el retardo procesal - Sarango Martínez, Glenda María (2022)
The present thesis work is entitled: “Determination of the term to initiate the administrative processing of the semi-open regime to guarantee the due process and avoid procedural delay”, from which arises the interest to investigate since there is a notable unjustified delay in the processing of the semi-open regime where the people deprived of liberty see their rights violated despite belonging to group of priority attention in which the State through its public dependencies must guarantee and materialize these rights that are inherent to them. In the national reality, the Ecuadorian Penitentiary System is going through a crisis, it is necessary to provide a viable alternative to this problem, such as the timely granting of the semi-open regime, helping to reduce prison overcrowding in a suitable way. Prison overcrowding is not only the congestion of people inside the penitentiary centers, but this problem brings with it violence, riots, lack of sanitation, lack of adequate rehabilitation and the spread of diseases among prisoners, in contravention of the precepts established in the Constitution of the Republic of Ecuador. In the present thesis, materials and methods were applied to allow the development of the investigation, as well as interviews and surveys to legal professionals, the results obtained were used to propose the legal reform to the Organic Integral Penal Code with the purpose of incorporating a reasonable term in Art. 698 to begin the administrative processing of semi-open regime in advance of the percentage of completion of the sentence required by law.